Qualitative exploration of women's experiences of intramuscular pethidine or remifentanil patient-controlled analgesia for labour pain. Issue 12 (23rd December 2019) - Moran, Victoria Hall; Thomson, Gillian; Cook, Julie; Storey, Hannah; Beeson, Leanne; MacArthur, Christine; Wilson, Matthew
Abstract : Objectives: To explore women's experiences of remifentanil or pethidine for labour pain and infant feeding behaviours at 6weeks post partum. Design: Qualitative postnatal sub-study to the randomised controlled trial of remifentanil intravenous patient controlled analgesia (PCA) versus intramuscular pethidine for pain relief in labour (RESPITE). Semistructured telephone interviews were conducted at 6 weeks post partum, and thematic analysis was undertaken. Setting: Women recruited to the RESPITE trial from seven UK hospitals. Participants: Eighty women consented and 49 (30 remifentanil group and 19 pethidine group) completed the interview. Results: Eight themes emerged which encompassed women's antenatal plans for pain management ( Birth Expectations ) through to their future preferences for pain relief ( Reflections for Future Choices ). Many women who used remifentanil felt it provided effective pain relief ( Effectiveness of Pain Relief ), whereas women in the pethidine group expressed more mixed views. Both groups described side effects, with women using pethidine frequently reporting nausea ( Negative Physiological Responses ) and women using remifentanil describing more cognitive effects ( Cognitive Effects ). Some women who used remifentanil reported restricted movements due to technical aspects of drug administration and fear of analgesia running out ( Issues with Drug Administration ). Women described how remifentanil enabled them to maintain their ability to stay focused during the birth ( Enabling a Sense of Control ). There was little difference in reported breastfeeding initiation and continuation between pethidine and remifentanil groups ( Impact on Infant Behaviour and Breastfeeding ). Conclusions: Qualitative insights from a follow-up study to a trial which explored experiences of intravenous remifentanil PCA with intramuscular pethidine injection found that remifentanil appeared to provide effective pain relief while allowing women to remain alert and focused during labour, although as with pethidine, some side effects were noted. Overall, there was little difference in reported breastfeeding initiation and duration between the two groups. Trial registration number: ISRCTN29654603 .